The re-emergence of educational inequality during a period of reforms: A study of Swedish school leavers 1991–2012. (May 2021) - Andersson, Eva K; Hennerdal, Pontus; Malmberg, Bo
Against the background of a liberalization of Swedish compulsory education, this paper analyses post-1991 shifts in the way compulsory education performance in Sweden has been shaped by parental background, residential context and school context. We can document increasing school and residential segregation of foreign background students and, after 2008, increasing segregation by income, employment status and social allowance reception. Over time, educational performance has become increasingly linked to family, neighbourhood and school context. The greatest change has been for parental background, but the importance of school context and neighbourhood context has also increased. A noteworthy finding is that residential context consistently has a stronger effect on student performance than school context. Student grades were found to be most strongly influenced by the closest (12 or 25) residential peers of the school leavers as compared to larger peer groups. The increase in the influence of family, neighbourhood and residential context has been accompanied by a dramatic increase in the between-school variation (intra-class correlation) in student performance, but it was not until after 2005 that this increased variability became clearly linked to the social composition of the schools. This study's results suggest that the restructuring of Swedish compulsory education has had consequences for equality, possibly because disadvantaged social groups have not been as able as advantaged groups to navigate and benefit from the educational landscape created by the school reforms.